The Relationship Between Industrial Work Practice And Family Environment On Entrepreneurial Interest of SMKN 4 Makassar - Tahir, Sumiati; Mahmuddin, Mahmuddin; Wisudawaty, Ika; Pahrul, Pahrul; Hasbi, Hasbi (International Journal of Education, Vocational and Social Science, 2024)
This study focuses on entrepreneurial motivation among students of SMK Negeri 4 Makassar, Makassar City, with the main objective of investigating two important aspects: first, the level of entrepreneurial motivation shown by students, and second, the influence of Industrial Work Practice (Prakerin) and family environment on the motivation. In the context of vocational education, the understanding of entrepreneurial motivation is becoming increasingly relevant, especially in preparing students to enter the world of work and contribute to economic development. The methodology used in this study is quantitative descriptive, which aims to strengthen theoretical propositions through empirical observations. Data were collected through a variety of techniques, including observation, surveys, interviews, and documentation, and analyzed using inferential statistical approaches, including classical assumption testing and double linear regression analysis. The results showed that students at SMK Negeri 4 Makassar have a high level of entrepreneurial motivation, and there is a significant correlation between Industrial Work Practice and family environment with students' entrepreneurial motivation. These findings highlight the importance of support from the family environment and practical experience in increasing students' interest in entrepreneurship, thus making an important contribution to the development of entrepreneurship education programs at the SMK level.